Modeling the toroidal asymmetry of the heat load impacted by nitrogen injection in EAST using EMC3-EIRENE. (15th September 2021) - Luo, Yang; Liu, Haifeng; Xu, Yuhong; Feng, Yuhe; Guo, Wenfeng; Dong, Chunfeng; Wang, Xianqu; Huang, Jie; Liu, Hai; Zhang, Xin; Li, Wei; Yang, Lang; et al.
Abstract: The effects of nitrogen injection on the heat load in the scape-off layer are systematically investigated in the EAST double-null divertor configuration using EMC3-EIRENE code. Nitrogen impurities injected near the separatrix line and away from the separatrix line give rise to a non-axisymmetric distribution of heat load on the target plate. With impurity injection near the separatrix line, the occurrence of the toroidal asymmetric heat load is observed only nearby the toroidal injection location, while with injection away from the separatrix line the regions of the asymmetric heat load extend and deviate from the toroidal injection position. The competition between the friction force and the ion temperature gradient force has been analyzed. It shows that when impurities are injected away from the separatrix line more impurities can be parallelly transported to a further toroidal location, which results in the extension and deviation of the non-symmetric electron temperature. When the input power is increased, the non-symmetric phenomenon of the heat load turns to be insignificant due to the reduction of the impurity density in the downstream regions, as illustrated by the field line tracing technique. Furthermore, by scanning various injection positions in the EAST tokamak, the optimum location of impurity injection has been discovered.